Jenis dan Populasi Serangga Pada Insect Hotel di Berbagai Jenis Lahan Pertanian - Najiyah, Aliyatul; Adhani, Rasyiqah; Megasari, Dita (Universitas Sebelas Maret, 2025)
Insect hotels are a medium for the conservation of beneficial insects that can be developed in the community. Insect hotels are developed to provide a safe and comfortable habitat for insects, especially beneficial insects. This research aims to determine the types and populations of insects in insect hotels across different types of land, namely rice fields, plantations, greenhouses, and agroforestry. The research was conducted by installing insect hotels in various types of agricultural land for one month, with observations made once a week. The observed insects in the insect hotels were then identified, and the average population count was calculated. The research results show that the types of insects obtained from the installation of insect hotels in rice fields, plantations, and greenhouses belong to the Formicidae family, while in agroforestry land, several types of insect families were found, namely the Coccinellidae, Anthocoridae, Aradidae, Tenebrionidae, Dolichopodidae, and Formicidae families. The Formicidae family was found in all agricultural lands with different average populations. The Formicidae family with the highest average population was found in the plantation land with a value of 4.75 individuals, while the lowest average population was found in the greenhouse and agroforestry land with a value of 0.5 individuals. The Tenebrionidae family was the family with the highest average population found in agroforestry land with an average of 2.75 individuals, while the family with the lowest average population found in agroforestry land was the Formicidae family with an average value of 0.5 individuals.